Paracecal appendicitis in a rare anatomical position: a case report describing a modified laparoscopic approach - Tran, Loc H.; Nguyen, Anh T. (International Journal of Research in Medical Sciences, 2025)
Anatomical variations of the appendix, such as a paracecal adherent position, are uncommon and may complicate both diagnosis and surgical management. While laparoscopic appendectomy remains the gold standard, this variant poses challenges in mobilization, vascular control, and cecal protection. We describe a 47-year-old female presenting with acute appendicitis, where contrast-enhanced computed tomography (CT) revealed a retrocecal appendix with paracecal adherence. At laparoscopy, necrotizing appendicitis in an unusual paracecal position was confirmed. A modified surgical strategy was applied, combining retrograde appendectomy with a lateral-to-medial dissection. This approach facilitated early vascular control, safe mobilization of the appendix, and secure division of the base without the use of staplers or endoloops. The operative time was 60 minutes, with minimal blood loss, and the patient had an uneventful recovery, being discharged on postoperative day three. Paracecal adherence represents a rare but technically demanding variant. Our combined retrograde and lateral-to-medial approach provided advantages in hemostasis, cecal protection, and operative efficiency. Compared to conventional methods, it minimized the risk of bleeding and avoided cecal injury, while also being cost-effective. This case highlights the feasibility and safety of a modified laparoscopic technique for paracecal adherent appendicitis. Broader validation in larger cohorts is warranted, but this strategy may represent a valuable alternative for surgeons encountering rare anatomical variants.